2017
DOI: 10.1177/1352458517711568
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evidence of oxidative stress in brains of patients with progressive multiple sclerosis

Abstract: Markedly lower GSH in progressive MS than RRMS indicates more prominent involvement of oxidative stress in the progressive stage of MS than the inflammatory stage. The association between GSH and brain atrophy suggests the important role of oxidative stress contributing to neurodegeneration in progressive MS, as suggested in other neurodegenerative diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 36 publications
4
61
1
Order By: Relevance
“…Higher levels of oxidative stress markers and lower antioxidant capacity have been found in MS patients. Some mechanisms have been proposed to explain the role of ROS in MS neurological damage including: (i) low levels of antioxidants that stimulate transendothelial leukocyte migration through the BBB breakdown, thus contributing to immunoinflammatory processes in the cerebral cortex; and (ii) excess ROS increasing T cell concentration and producing myelin damage [ 56 , 90 , 91 , 92 ]. Nrf2 is also involved in the progression of MS, although studies with dietary compounds are scarce.…”
Section: Nuclear Factor (Erythroid-derived 2)-like 2 (Nrf2) and Nementioning
confidence: 99%
“…Higher levels of oxidative stress markers and lower antioxidant capacity have been found in MS patients. Some mechanisms have been proposed to explain the role of ROS in MS neurological damage including: (i) low levels of antioxidants that stimulate transendothelial leukocyte migration through the BBB breakdown, thus contributing to immunoinflammatory processes in the cerebral cortex; and (ii) excess ROS increasing T cell concentration and producing myelin damage [ 56 , 90 , 91 , 92 ]. Nrf2 is also involved in the progression of MS, although studies with dietary compounds are scarce.…”
Section: Nuclear Factor (Erythroid-derived 2)-like 2 (Nrf2) and Nementioning
confidence: 99%
“…Despite the poorly understood etiology of MS, it has been suggested that genetic background and environmental factors may both act as the main drivers of the disease . Several studies have shown that inflammatory factors and oxidative stress play a significant role in the development of demyelination, which occurs through the generation of nitrogen‐ and oxygen‐free radicals as well as the formation of oxidized phospholipids . The oxidative stress caused by these free radicals, such as reactive oxygen species (ROS) and reactive nitrogen species, as toxic reagents to nerve cells, destroys and disrupts their function and plays a key role in the pathological processes of several neurological disorders, such as MS and Alzheimer's disease .…”
Section: Introductionmentioning
confidence: 99%
“…Most of them, but not the n-3 PUFAs, are antioxidants, which make them very useful, as oxidative stress is an important component of the inflammatory processes leading to degradation of myelin and axonal damage. Oxidative stress and inflammation are present in relapsing-remitting and in primary and secondary progressive MS [60,61].…”
Section: Anti-inflammatory Dietary Molecules and Microorganismsmentioning
confidence: 99%